Method for quantitatively determining fusibility of volcanic ash
By heating the volcanic ash column on the thermal barrier coating material and collecting the geometric changes of its longitudinal section profile, the melting interval of the volcanic ash is determined, and the problem of inaccurate determination of the molten ash in the prior art is solved, and the accurate melting temperature measurement of the volcanic ash is achieved.
Patent Information
- Application Number
- CN202510001826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-21
AI Technical Summary
It is difficult for the prior art to accurately determine the melting properties of volcanic ash, especially in natural volcanic ash with complex compositions. Traditional differential scanning calorimetry cannot effectively describe its melting temperature.
Porosity columns are prepared and placed on a block of thermal barrier coating material and heated to melt. During the heating process, high-temperature contact angle equipment is used to collect geometric changes in the longitudinal section profile, analyze the dynamic changes in shape factors and height, and determine the deformation temperature and flow temperature, thereby defining the melting interval of the volcanic ash.
Quantitative determination of the melting temperature interval of volcanic ash is achieved, suitable for natural volcanic ash with complex compositions, providing more accurate basic data to study its hazards to thermal barrier coatings.
Smart Images

Figure CN119666909A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material thermal protection, and in particular to a method for quantitatively determining the fusibility of volcanic ash. Background Art
[0002] With the development of aviation technology, the thrust-to-weight ratio of aircraft engines has been increasing, achieving high efficiency and low fuel consumption, but also leading to a continuous increase in the inlet temperature of the turbine. In the future, the inlet temperature of the turbine may reach as high as 1650°C. Therefore, thermal barrier coatings need to be applied to the hot end components of aircraft engines to block heat and protect the high-temperature alloy at the bottom.
[0003] The dust in the atmosphere contains volcanic ash. After being sucked into the engine, it hits the surface of the thermal barrier coating and quickly melts into droplets at high temperature and adheres to the coating. Then it wets and spreads on the coating surface, and finally penetrates into the coating along the inter-column gaps, voids and active cracks in the thermal barrier coating structure. This physical process largely determines the area of corrosion of the thermal barrier coating surface by the molten volcanic ash and the scope and degree of the final mechanical damage and chemical reaction. The coverage of molten volcanic ash will eventually lead to premature failure of the ceramic layer of the thermal barrier coating due to microstructural instability, deformation and peeling. The process of wetting, spreading and penetration of volcanic ash on the surface of the thermal barrier coating is mainly affected by the high-temperature physical properties of the volcanic ash itself, especially the molten ash meltability. Therefore, the determination of the molten ash meltability is of great significance to the research on thermal barrier coatings for aircraft engines.
[0004] However, the physical properties and chemical composition of volcanic ash are extremely wide, and the composition of volcanic ash in different locations varies greatly, which also leads to different fusibility of various volcanic ashes, making it difficult to uniformly measure. In addition, the composition of volcanic ash is complex, with 10 kinds of oxides, and there are both crystalline phase and glass phase inside. The glass phase has a low transition temperature of 500-800℃, which is much lower than the operating temperature of the engine of 1200℃, while the crystal phase has a high melting point, which makes it difficult to obtain the fusibility of volcanic ash using traditional measurement methods for a single phase in the crystal phase or glass phase.
[0005] In previous studies, researchers mostly used differential scanning calorimetry (DSC) to study the fusibility of volcanic ash, and selected the temperature corresponding to the peak value with the highest heat absorption as the melting temperature of volcanic ash. However, volcanic ash has a complex composition, and its melting is not completed in an instant, but a slow heat exchange. It is inaccurate to use a certain temperature to describe the melting temperature of volcanic ash, and it is difficult to support subsequent research on the harm of volcanic ash to thermal barrier coatings. In addition, the DSC curves of many natural volcanic ashes do not have obvious endothermic peaks, making it difficult to determine their fusibility by differential scanning calorimetry. Therefore, it is urgent to find a better method to redefine and measure the fusibility of volcanic ash. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for quantitatively determining the fusibility of volcanic ash, the method comprising the following steps:
[0007] 1) Prepare volcanic ash columns.
[0008] 2) A group of samples is obtained by placing a volcanic ash column on a block of thermal barrier coating material, and the group of samples is placed on a sample holder embedded with a thermocouple, and heated to melt the volcanic ash column. Before and during heating, a high-temperature contact angle device is used to collect in situ the geometric changes of the longitudinal section profile of the group of samples as the temperature changes.
[0009] 3) Based on the collected data, the dynamic changes of the shape factor f and the height H of the volcanic ash column with temperature are analyzed, so that the temperature when f changes by 15% relative to the temperature before heating is determined as the deformation temperature, the temperature when H is 1 / 3 of the temperature before heating is determined as the flow temperature, and the interval with the deformation temperature and the flow temperature as endpoints is determined as the volcanic ash melting interval.
[0010] The shape factor f is obtained by the following formula:
[0011]
[0012] Among them, A is the longitudinal cross-sectional area of the volcanic ash sample, and U is the circumference of the longitudinal cross-sectional area of the volcanic ash sample.
[0013] In some embodiments, the volcanic ash column is a cylinder with a diameter of 1-3 mm.
[0014] In some embodiments, the step of preparing a volcanic ash column comprises:
[0015] a) Sample loading: Place the ground volcanic ash powder into the mold and compact it with a retractable press head.
[0016] b) Powder blowing: clean the excess volcanic ash powder outside the mold.
[0017] c) Compaction: Use a fixed pressure head to compact the volcanic ash powder again.
[0018] d) Remove the upper layer: Rotate the mold to remove the ash blocks on the upper layer and keep the ash blocks in the middle mold.
[0019] e) Sampling: Use a demoulding tool of corresponding size to push out the compacted volcanic ash blocks.
[0020] In some embodiments, the thermal barrier coating material is gadolinium zirconate ceramic.
[0021] In some embodiments, before heating the set of samples to melt the ash columns therein, the method further comprises: placing the set of samples on a sample holder with a thermocouple inserted therein, wherein the thermocouple is used to monitor the temperature.
[0022] In some embodiments, during heating, the heating is performed from room temperature to 1000° C. at a rate of 10 k / min, and from 1000° C. at a rate of 5 k / min until the ash column melts.
[0023] In some embodiments, the acquisition of geometric changes in the longitudinal cross-sectional profile of the group of samples as the temperature changes is achieved by a charge-coupled device camera with an acquisition frequency of 1 Hz.
[0024] The method provided by the invention can quantitatively determine the melting temperature range of volcanic ash and can be applied to natural volcanic ash with complex components. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 A flow chart of a method for quantitatively determining the fusibility of volcanic ash provided by the present invention;
[0027] Figure 2 It is a schematic diagram of the geometric characteristics of the longitudinal section profile of the sample at the key temperature point;
[0028] Figure 3 Schematic diagram of the geometric meaning of the shape factor f in the present invention;
[0029] Figure 4 A DSC curve of an artificially synthesized volcanic ash CMAS provided in an embodiment of the present invention;
[0030] Figure 5 A characteristic longitudinal cross-sectional profile of a CMAS sample provided in an embodiment of the present invention and its corresponding key temperature points (unit: °C);
[0031] Figure 6 DSC curves of seven natural volcanic ashes provided in the embodiments of the present invention;
[0032] Figure 7 Characteristic longitudinal section profiles of six natural volcanic ash and CMAS samples provided in the embodiments of the present invention and their corresponding key temperature points (unit: °C). DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0034] The present invention provides a method for quantitatively determining the fusibility of volcanic ash. Each step of the method is explained in detail below in conjunction with the accompanying drawings and specific embodiments. Figure 1 As shown, the method includes the following three steps:
[0035] Step 1: Prepare the volcanic ash column, which can be carried out according to the following sub-steps:
[0036] a) Sample loading: The ground volcanic ash powder is placed in a mold and compacted with a retractable pressing head. The columnar mold is a cylinder with a diameter of 3 mm.
[0037] b) Powder blowing: clean the excess volcanic ash powder outside the mold.
[0038] c) Compaction: Use a fixed pressure head to compact the volcanic ash powder again.
[0039] d) Remove the upper layer: Rotate the mold to remove the ash blocks on the upper layer and keep the ash blocks in the middle mold.
[0040] e) Sampling: Use a demolding tool of corresponding size to push out the compacted volcanic ash blocks to obtain volcanic ash columns.
[0041] Step 2: Place the volcanic ash column on the thermal barrier coating material block to obtain a group of samples, heat the group of samples to melt the volcanic ash column; and before and during heating, use a high-temperature contact angle device to in-situ collect the geometric changes of the longitudinal section profile of the group of samples as the temperature changes.
[0042] As described in the background technology, the present invention determines the fusibility of volcanic ash to provide a basis for the research of thermal barrier coatings for aircraft engines, so a thermal barrier coating material is selected as the substrate. The thermal barrier coating material can be GYbZ ceramics.
[0043] Before heating, the set of samples can be placed on a sample holder embedded with a thermocouple, where the thermocouple can be used to monitor temperature data.
[0044] During heating, the temperature was heated from room temperature to 1000°C at a rate of 10 k / min, and from 1000°C to the melting of the ash column at a rate of 5 k / min. In previous studies, it was found that there was no obvious physical / chemical change in ash below 1000°C, so rapid heating was used below 1000°C to save time; slow heating was used above 1000°C to better collect the geometric changes of the longitudinal cross-section profile of the ash during the melting process as the temperature changes.
[0045] The high temperature contact angle device can collect the morphology of the droplet on the solid surface in situ under high temperature environment. In some embodiments, the high temperature contact angle device includes a charge coupled device (CCD) camera. When collecting data, the charge coupled device camera collects the geometric changes of the longitudinal section profile of the sample at a rate of 1 Hz, including the changes in height, area, perimeter, contact angle and spreading radius relative to temperature and time. Each group of samples is tested twice to eliminate the accidental nature of the experiment.
[0046] After heating, the temperature was lowered at a rate of 50 k / min, and the sample was taken out after cooling to room temperature.
[0047] Step 3: Based on the collected data, analyze the dynamic changes of the longitudinal section profile of the volcanic ash column sample as the temperature changes.
[0048] Specifically, it is necessary to find the longitudinal section profile image of the volcanic ash sample that meets specific geometric characteristics based on the collected data, so as to determine the key temperature points in the melting process and then determine the melting range of the volcanic ash. Figure 1 As shown, the key temperature points and their corresponding contour geometric features include:
[0049] (1) Deformation temperature (DT) - the temperature at which the shape factor f of the longitudinal section of the sample changes by 15% relative to the original value at room temperature. This temperature is regarded as the starting temperature of volcanic ash melting.
[0050] The shape factor f describes the consistency of the sample contour geometry with its ideal semicircle, and its geometric meaning is as follows: Figure 2 As shown, it is defined as:
[0051] Create an ideal semicircle so that its area A(semicircle) is equal to the area A(x) of the longitudinal section of the volcanic ash sample, that is, A(x) = A(semicircle). Then the shape factor Among them, U(semicircle) is the circumference of this ideal semicircle, and U(x) is the circumference of the longitudinal section of the volcanic ash sample.
[0052] According to this definition, if the radius of the ideal semicircle is recorded as r, we can get: Right now but Then the shape factor:
[0053]
[0054] When the sample is in a perfect semicircular shape, the shape factor f=1.0, when the sample is in other shapes, f<1.0, and when the sample is in an ideal square, f=0.836.
[0055] (2) Hemisphere temperature (HT) - The height of the profile is equal to half the diameter of the profile base. At this time, the contact angle between the molten ash droplet and the substrate is 90°.
[0056] (3) Flow temperature (FT) - The height of the profile is 1 / 3 of the original value at room temperature. This temperature is regarded as the end temperature of volcanic ash melting.
[0057] Wherein, DT is the starting temperature of volcanic ash melting, FT temperature is the ending temperature of volcanic ash melting, and ΔT=FT-DT is the melting range of volcanic ash.
[0058] The above specifically introduces the method steps for quantitatively determining the fusibility of volcanic ash provided by the present invention, and the specific implementation results are listed below.
[0059] 1. The sample is an artificially synthesized CMAS containing four oxides.
[0060] As a control, the melting point of CMAS was determined by DSC. The DSC curve of CMAS is shown in Figure 3 As shown, its melting point is 1236°C at the peak temperature.
[0061] The melting point of CMAS is determined by the method provided by the present invention. The characteristic longitudinal section profile of the CMAS sample and its corresponding key temperature point (unit: °C) are as follows: Figure 4 As shown. It can be seen that the melting range of CMAS measured by the method provided by the present invention is 1240°C-1244°C, which is different from the DSC endothermic peak temperature of CMAS. The reason is that during the DSC test, the artificially synthesized CMAS is in contact with the pt crucible, and when the solubility is measured by the method provided by the present invention, the CMAS is in contact with the surface of the gadolinium zirconate block. The contact materials of the two measurement methods are different. The melting temperature mainly depends on the interaction force between molecules. The change of the matrix material will affect the melting temperature of the artificially synthesized CMAS, but the results are not much different.
[0062] 2. The sample is natural volcanic ash collected from volcanic eruptions.
[0063] As a control, the melting points of six natural volcanic ashes, TMJ, TJ, EKS, HKSC, Ejya, and Fuego, were determined by DSC. Their DSC curves are shown in Figure 5 As shown, it can be seen that their DSC curves have no obvious endothermic peaks and no fixed melting points, indicating that DSC cannot determine the fusibility of these natural volcanic ashes.
[0064] The melting points of six natural volcanic ashes, TMJ, TJ, EKS, HKSC, Ejya and Fuego, were determined by the method provided by the present invention. The characteristic longitudinal section profiles of the samples and their corresponding key temperature points (unit: °C) are shown in the figure. Figure 6 As shown. Figure 6 , the melting ranges of these natural volcanic ashes can be obtained, as shown in Table 1.
[0065] Table 1 Melting range of natural volcanic ash
[0066]
[0067] It can be seen from the above that the method provided by the present invention can quantitatively determine the melting temperature range of volcanic ash and can be applied to natural volcanic ash with complex components.
[0068] In the description of the embodiments of the present application, words such as "exemplary", "for example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary", "for example" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary", "for example" or "for example" is intended to present related concepts in a concrete way.
[0069] In the description of the embodiments of the present application, the term "and / or" is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, B exists alone, and A and B exist at the same time. In addition, unless otherwise specified, the term "plurality" means two or more.
[0070] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. The terms "include", "comprises", "has" and their variations all mean "including but not limited to", unless otherwise specifically emphasized.
[0071] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made on the basis of the technical solution of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for quantitatively determining the fusibility of volcanic ash, characterized in that: The following steps are involved: preparing ash columns; Placing a volcanic ash column on a block of a thermal barrier coating material to obtain a group of samples, and heating the group of samples to melt the volcanic ash column therein; Before and during heating, a high-temperature contact angle device was used to collect in situ the geometric changes of the longitudinal cross-sectional profile of the group of samples as the temperature changes; According to the collected data, the dynamic changes of the shape factor f and the height H of the volcanic ash column with temperature are analyzed, so as to determine the temperature when f changes by 15% relative to the temperature before heating as the deformation temperature, the temperature when H is 1 / 3 of the temperature before heating as the flow temperature, and the interval with the deformation temperature and the flow temperature as endpoints as the volcanic ash melting interval; The shape factor f is obtained by the following formula: Among them, A is the longitudinal cross-sectional area of the volcanic ash sample, and U is the circumference of the longitudinal cross-sectional area of the volcanic ash sample.
2. The method according to claim 1, characterized in that The volcanic ash column is a cylinder with a diameter of 1-3 mm.
3. The method according to claim 1, characterized in that The method for preparing a volcanic ash column comprises: Loading the sample, putting the ground volcanic ash powder into the grinding tool, and compacting the volcanic ash powder with a retractable pressing head; Blow the powder to clean the excess volcanic ash powder outside the mold; Compacting: using a fixed pressure head to compact the volcanic ash powder again; Remove the upper layer, rotate the mold, remove the ash blocks on the upper layer, and keep the ash blocks in the middle mold; Take samples and use a demolding tool of corresponding size to push out the compacted volcanic ash blocks.
4. The method according to claim 1, characterized in that: The thermal barrier coating material is gadolinium zirconate ceramic.
5. The method according to claim 1, characterized in that: Prior to heating the set of samples to melt the ash columns therein, the method further comprises: The set of samples was placed in a sample holder with a thermocouple inserted in the front for monitoring the temperature.
6. The method according to claim 1, characterized in that During heating, the temperature was heated from room temperature to 1000°C at a rate of 10 k / min, and from 1000°C to the melting of the volcanic ash column at a rate of 5 k / min.
7. The method according to claim 1, characterized in that The acquisition of geometric changes in the longitudinal cross-sectional profile of the group of samples as the temperature changes is achieved by a charge-coupled device camera with an acquisition frequency of 1 Hz.
Citation Information
Patent Citations
Test device and test method of wetting performance of fusion CMAS erosion thermal barrier coating
CN105241791A
Method for detecting CMAS high-temperature corrosion of thermal barrier coating
CN109883938A
Measurement method for porosity of irregular columnar structure of thermal barrier coating
WO2024120071A1